2021
DOI: 10.1002/cssc.202100627
|View full text |Cite
|
Sign up to set email alerts
|

Achieving over 10 % Efficiency in Poly(3‐hexylthiophene)‐Based Organic Solar Cells via Solid Additives

Abstract: The photovoltaic performance of organic solar cells (OSCs) based on poly(3-hexylthiophene) (P3HT) has been steadily improved by developing novel non-fullerene acceptors (NFAs) in recent years. Herein, to further improve the performance of P3HT-based OSCs, a solid additive (SA4) and a typical solvent additive [1,8-diiodooctane (DIO)] were employed to process P3HT:ZY-4Cl-based OSCs, respectively. In comparison with the DIO-processed device, the SA4-processed one exhibited a more ordered molecular packing and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Recently, it has been demonstrated that the PCE of the P3HT based OSCs could be significantly increased using ZY-4Cl, with the chemical structure very similar to that of Y6 (Fig. S1, Supporting Information), as the acceptor material (PCE ≈ 10.24%) 55 . This is one of the highest PCE values realized for the OSCs based on P3HT 22,23,26,33 .…”
Section: Reducing Knr In the P3ht:nfa Oscsmentioning
confidence: 99%
“…Recently, it has been demonstrated that the PCE of the P3HT based OSCs could be significantly increased using ZY-4Cl, with the chemical structure very similar to that of Y6 (Fig. S1, Supporting Information), as the acceptor material (PCE ≈ 10.24%) 55 . This is one of the highest PCE values realized for the OSCs based on P3HT 22,23,26,33 .…”
Section: Reducing Knr In the P3ht:nfa Oscsmentioning
confidence: 99%
“…23 Later, they further pushed the PCE to 10.24% by preparing ternary devices with a third solid additive. 24 What's more, alternatives were designed, such as the P3HT derivative P4T2F-FD with electron-withdrawing fluorine atoms attached to the skeleton, which result in a lower HOMO. This donor yielded the highest PCE of 13.34% when combined with the Y6-BO acceptor in nonhalogenated solvent.…”
Section: The Development Of New Donor and Acceptor Materials In The Oscsmentioning
confidence: 99%
“…[80] After precise control of the molar mass, the PCE was further improved to 9.60% when using P3HT with medium molar mass batch (25.5 kg/mol). Very recently, we continued to optimize the molecular packing and phase separation of P3HT:ZY-4Cl-based blend film by applying a volatilizable [81] In comparison with the widely used additive 1,8-diiodooctane, SA4 exhibited similar effects on the optical and crystalline characteristics of P3HT and ZY-4Cl but totally different on the morphology of their blend film. In-depth investigation revealed that SA4 could induce the enhanced molecular packing and superior phase separation in the blend film, which were conducive to the enhanced J SC and FF.…”
Section: Oscs Based On P3htmentioning
confidence: 99%